Numerical Simulation of Airfoil Vibrations Induced by Turbulent Flow (Communications in Computational Physics, 2018)
The subject of the paper is the numerical simulation of the interaction oftwo-dimensional incompressible viscous flow and a vibrating airfoil with large amplitudes.The airfoil with three degrees of freedom performs rotation around an elasticaxis, oscillations in the vertical direction and rotation of a flap. The numerical simulationconsists of the finite element solution of the Reynolds averaged Navier-Stokesequations combined with Spalart-Allmaras or k−ω turbulence models, coupled with asystem of nonlinear ordinary differential equations describing the airfoil motion withconsideration of large amplitudes. The time-dependent computational domain andapproximation on a moving grid are treated by the Arbitrary Lagrangian-Eulerian formulationof the flow equations. Due to large values of the involved Reynolds numbersan application of a suitable stabilization of the finite element discretization isemployed. The developed method is used for the computation of flow-induced oscillationsof the airfoil near the flutter instability, when the displacements of the airfoilare large, up to ±40 degrees in rotation. The paper contains the comparison of thenumerical results obtained by both turbulence models.